Pengaruh Karakteristik Individu, Komunikasi, Dan Kerjasama Tim Terhadap Kinerja Pegawai - Agustin, Faikotul Wulan; Sunaryo, Hadi; Suharto, M. Khoirul Anwarudin Broto (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to describe and analyze the influence of individual characteristics, communication, and teamwork on employee performance. The type of research used in this study is quantitative research. The population in this study were employees of Field 1 of the Pasuruan Regency Environmental Service. The determination of the number of samples used saturated samples with a total of 83 employees as respondents. The results of the study stated that individual characteristics, communication, and teamwork simultaneously influenced employee performance and partially individual characteristics and teamwork had a positive and significant effect on employee performance while communication did not affect employee performance. Keywords: Individual Characteristics, Communication, Teamwork, Employee Performance